Gypsum and potassium application to acid soils for maize (Zea mays L.) production in La Frailesca, Chiapas, Mexico = Aplicación de yeso y potasio a suelos ácidos para producir maíz (Zea mays L.) en La Frailesca, Chiapas, México - Tasistro, Armando; Camas Gómez, Robertony; Ortiz Monasterio, Iván (2022)
Introduction. Maize (Zea mays L.) production in La Frailesca region, Mexico, is limited by sandy soils, low in potassium (K), and with acidic arable layers and subsoils. There is information on the management of lime but not on amendments that could be used for subsoil acidity - such as gypsum - nor on the interactions between amendments for soil acidity and K fertilization. Objective. To evaluate the effects of K and gypsum on maize and on previously limed soils. Materials and methods. The evaluations were conducted in farmers' fields in La Frailesca region, Chiapas (Mexico) in 2016 and 2017. Four gypsum rates (0, 1.25, 2.5 and 5 t ha-1) and four K rates (0, 60, 90, and 120 kg ha-1 as K2O) were factorially combined in a randomized block design, with three replicates. In both years, before the beginning of the experiments, dolomitic lime was applied to the experimental area following standard practices. Responses of crop yield, soil exchangeable K, Ca, Mg, and Al, and soil pH were obtained. Results. Maize yields increased with gypsum (stabilizing at 1.25-3.0 t ha-1), and K (stabilizing at 70-120 kg ha-1 of K2O) applications. In soils, K application increased exchangeable K content, while gypsum increased exchangeable Ca content and pH, and decreased exchangeable Al content. Liming increased pHCa and exchangeable Ca and Mg contents, and lowered the exchangeable Al content in the top 7.5 cm of soil. Conclusion. Soils with exchangeable K (≤0.3 cmolc kg-1) were responsive to K fertilization. The positive effects on yields from gypsum were probably linked to a greater Ca supply in the top 7.5 cm. These results are encouraging about the benefits of the combined application of dolomitic lime, gypsum, and K, but longer evaluations are needed to properly determine the effects of gypsum on subsoil acidity.
Introducción. La producción de maíz (Zea mays L.) en la región de La Frailesca, México, está limitada por suelos arenosos, bajos en K y con capas arables y subsuelos ácidos. Existe información sobre el manejo de cal, no así de enmiendas como el yeso que servirían para la acidez del subsuelo, ni sobre las interacciones entre tales enmiendas y la fertilización potásica. Objetivo. Evaluar los efectos del K y el yeso en maíz y en suelos previamente encalados. Materiales y métodos. Las evaluaciones se realizaron en campos de agricultores en La Frailesca, Chiapas (México) en 2016 y 2017. Se combinaron factorialmente cuatro dosis de yeso (0, 1,25, 2,5 y 5 t ha-1) y cuatro de K (0, 60, 90, y 120 kg ha-1 como K2O) en un diseño de bloques al azar, con tres repeticiones. En ambos años, antes de iniciar los experimentos, se aplicó cal dolomítica al área experimental con base en las prácticas estándar. Se obtuvieron las respuestas del rendimiento del cultivo, pH y K, Ca, Mg, y Al intercambiables del suelo. Resultados. El rendimiento del maíz aumentó al aplicar yeso (estabilizándose a 1,25-3,0 t ha-1) y K (se estabilizó a 70-120 kg ha-1 de K2O). En los suelos, la aplicación de K aumentó el K intercambiable, mientras que el yeso aumentó el Ca intercambiable y el pH, y disminuyó el Al intercambiable. El encalado aumentó el pHCa y los contenidos de Ca y Mg intercambiables y disminuyó el Al intercambiable en los 7,5 cm superiores. Conclusión. Suelos con K intercambiable (≤0,3 cmolc kg-1) respondieron al K. Los efectos del yeso sobre los rendimientos estuvieron probablemente relacionados con el aporte de Ca en los 7,5 cm superiores. Estos resultados indican posibles beneficios de la aplicación combinada de cal dolomítica, yeso y K, pero faltan evaluaciones de los efectos del yeso en la acidez del subsuelo.
En Revista Agronomía mesoamericana
Volumen 33, número 1 (enero - abril 2022)
Descripción basada en el contenido visto el 26 de Octubre, 2023
También disponible en formatos EPUB, HTML, XML y MP3 (español e ingles)
Keywords: MAIZ -- CULTIVO; RENDIMIENTO DE CULTIVOS -- EVALUACIÓN; SUELOS ACIDOS; SUELOS -- CONTENIDO DE CALCIO; SUELOS -- CONTENIDO DE YESO; SUELOS -- ABONOS Y FERTILIZANTES